2023
DOI: 10.21873/invivo.13163
|View full text |Cite
|
Sign up to set email alerts
|

Physiotherapy Efficiency in Post-stroke Upper Extremity Spasticity: TENSvs. Ultrasoundvs. Paraffin

Abstract: Background/Aim: Post-stroke spasticity is a significant debilitating condition with negative consequences on individual functional independence and quality of life. This study aimed to identify the differences between transcutaneous electrical stimulation (TENS), ultrasound therapy and paraffin procedures on post-stroke upper extremity spasticity and dexterity. Patients and Methods: Twenty-six patients were enrolled in the study, divided into three therapy groups: TENS (n=9), paraffin (n=10) and ultrasound the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…The mean scores in these areas showed significant reductions post-treatment, indicating a decrease in muscle spasticity. However, no significant differences were observed between the two groups when baseline measurements were compared, suggesting that both interventions were equally effective at the outset of the study (15,16). The lack of significant difference in baseline measures, with p > 0.05, implies that the initial conditions of spasticity in both groups were comparable, allowing for a fair comparison of the treatment effects.…”
Section: Discussionmentioning
confidence: 94%
“…The mean scores in these areas showed significant reductions post-treatment, indicating a decrease in muscle spasticity. However, no significant differences were observed between the two groups when baseline measurements were compared, suggesting that both interventions were equally effective at the outset of the study (15,16). The lack of significant difference in baseline measures, with p > 0.05, implies that the initial conditions of spasticity in both groups were comparable, allowing for a fair comparison of the treatment effects.…”
Section: Discussionmentioning
confidence: 94%
“…A meta-analysis examining the spasticityrelieving effect of TENS discovered that applying it to the muscle belly of spastic muscles for over 30 min effectively alleviated spasticity [17]. Additionally, a study comparing the spasticity-relieving effects of TENS, ultrasound, and paraffin reported that all three treatments had similar efficacy in relieving spasticity [30]. In this previous study, TENS was administered to the muscle belly of the plantar flexor for 30 min in both groups, resulting in significant improvements in stiffness for both.…”
Section: Discussionmentioning
confidence: 99%